Prudential Policy with Distorted Beliefs - Dávila, Eduardo; Walther, Ansgar (American Economic Review, 2023)
This paper studies leverage regulation when equity investors and/or creditors have distorted beliefs relative to a planner. We characterize how the optimal regulation responds to arbitrary changes in investors’/creditors’ beliefs, relating our results to practical scenarios. We show that the optimal regulation depends on the type and magnitude of such changes. Optimism by investors calls for looser leverage regulation, while optimism by creditors, or jointly by both investors/creditors, calls for tighter leverage regulation. Our results apply to environments with (i) planners with imperfect knowledge of investors’/creditors’ beliefs, (ii) monetary policy, (iii) bailouts and pecuniary externalities, and (iv) endogenous beliefs. (JEL D62, D83, E52, G01, G21, G28, H81)